2011
DOI: 10.1097/hjh.0b013e32834a4d03
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β inhibits myocardial PPARγ expression in pressure overload-induced cardiac fibrosis and remodeling in mice

Abstract: Objectives Pharmacological activation of peroxisome proliferator-activated receptor gamma (PPARγ) has been shown to attenuate pressure overload-induced cardiac fibrosis, suggesting that PPARγ has an antifibrotic effect. This study tested the hypothesis that there is a functional interaction between transforming growth factor-β (TGF-β) signaling and endogenous PPARγ expression in cardiac fibroblasts and pressure overloaded heart. Methods and results We observed that, in response to pressure overload induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Meanwhile, previous studies also demonstrated the TGFβ pathway crosstalks with PPARγ in such a way that TGFβ downregulates PPARγ expression and its downstream effectors 3032 , while PPARγ ligands counteracted TGFβ-mediated fibrosis 33 ; however, the crosstalk between TGFβ-Smad2 pathway and PPARγ remain unclear in CMs. Our results showed that overexpression of Smad2 decreased the expression of PPARγ in CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, previous studies also demonstrated the TGFβ pathway crosstalks with PPARγ in such a way that TGFβ downregulates PPARγ expression and its downstream effectors 3032 , while PPARγ ligands counteracted TGFβ-mediated fibrosis 33 ; however, the crosstalk between TGFβ-Smad2 pathway and PPARγ remain unclear in CMs. Our results showed that overexpression of Smad2 decreased the expression of PPARγ in CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Mice have decreased PPAR γ expression after TAC, which is reversed in mice when TGF β signaling is blocked [ 185 ]. Treatment of mice with rosiglitazone from 3 days before till 3 weeks after TAC decreased fibrosis and hypertrophy, whereas treatment with PPAR γ antagonist had the opposite effect [ 185 ].…”
Section: Cardiac Pathology: Involvement Of Ppar Isoforms In Protecmentioning
confidence: 99%
“…Mice have decreased PPAR γ expression after TAC, which is reversed in mice when TGF β signaling is blocked [ 185 ]. Treatment of mice with rosiglitazone from 3 days before till 3 weeks after TAC decreased fibrosis and hypertrophy, whereas treatment with PPAR γ antagonist had the opposite effect [ 185 ]. In rats with L-NAME induced hypertension, treatment with L-carnitine normalizes hypertension, hypertrophy, fibrosis, PPAR γ expression, and expression of fibrotic factors [ 186 ].…”
Section: Cardiac Pathology: Involvement Of Ppar Isoforms In Protecmentioning
confidence: 99%
“…siRNA-mediated inhibition of HDAC3 attenuated angiotensin II mediated reductions in PPARγ abundance in VSMCs [26]. TGF-β1 down-regulates PPARγ gene expression through recruitment of HDAC1 at the PPARγ promoter in cardiac fibroblasts [36]. Importantly, it has been reported that cytoplasmic IκBα increases NF-κB-independent transcription through binding to HDAC1 and HDAC3 [37].…”
Section: Discussionmentioning
confidence: 99%